Relationship of Risk Screening to HIV and Viral Hepatitis Detection for Participants in a Colorado Narcotic Replacement Therapy Program. (4th October 2017) - Hurley, Hermione; Gawenus, Lisa; Gardner, Edward M; Rowan, Sarah
Abstract: Background: Viral hepatitis is common among individuals who attend narcotic replacement therapy (NRT) programs, yet screening is not universally implemented. Programs may use behavioral risk questionnaires to determine whom to screen, though the efficacy of this approach has not been assessed. We compared risk score from the behavioral risk intake assessments at our institution's NRT program with the results of HIV and viral hepatitis tests, and analyzed the care continuum for HCV-diagnosed NRT participants. Methods: Retrospective chart review of NRT participants. All charts were reviewed for high-risk or risk-not-assessed individuals and a random subset of charts were reviewed for individuals determined to have medium or low risk. Intake viral screening, subsequent testing during NRT participation, evaluation and linkage to care for HCV, HBV and HIV were collected. Data was extrapolated to estimate baseline screening, prevalence and care continuum data among all NRT participants. Results: As of October 2016, 866 individuals were enrolled in NRT. 27% of the charts reviewed had full HIV/HCV/HBV screening completed at intake. Overall, 33% of individuals were tested for HIV and 1 individual tested positive; 46% of individuals were tested for HBV and 1 individual tested positive; and 47% were tested for HCV Ab, of which 37% tested positive. By risk behavior questionnaires, 4% of individuals were considered high risk for viral infection, 54% medium risk, 34% low risk, and 8% not assessed. See Figure 1. The percentage of positive HCV tests was high across all risk groups (26%-58%). 150 individuals in the entire cohort were estimated to have been diagnosed HCV RNA+ (37% of those tested, 14% of all participants); 7 were treated and cured (6% of those RNA+). See Figure 2. Conclusion: Participants in the NRT program had low rates of HIV and HBV and high rates of HCV exposure across all behavioral risk levels. 14% of the cohort were diagnosed with active HCV, though fewer than half of the participants were tested. HCV referral, linkage and treatment rates were low across all subgroups; interventions to expand testing to all intakes regardless of risk score and optimize linkage to care could greatly impact diagnosis and treatment rates among this high-prevalence population. Disclosures: All authors: No reported disclosures.